(untitled) (Scientific journal of the Fergana State University, 2025)
This article studies and analyzes the migration process of the population and its territorial composition in the Surkhandarya region, as well as presents ideas and comments on the theoretical foundations of studying the migration process. In particular, the formation of external migration of the population in the Surkhandarya region and the factors influencing its development are discussed. Also, this research work provides a brief description of the study of the migration process by foreign and Uzbek scientists.